Implementasi Model Problem-Based Learning dengan Media “TASUKA” untuk Meningkatkan Keterampilan Menulis Siswa Sekolah Dasar - Effiana Cahya Ningrum (SITASI: Journal of Islamic Studies and Inclusive Education, 2026)
The low level of early writing skills among students requires teachers to employ instructional models and media that can effectively support the improvement of these abilities. One approach utilized in this study is the implementation of the Problem-Based Learning (PBL) model combined with the TASUKA (Taman Suku Baca) instructional media. This research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. Data analysis was conducted through the stages of data collection, data reduction, data display, and conclusion drawing. The research subjects consisted of 29 first-grade students and one Indonesian language teacher. The findings indicate that the application of the PBL model assisted by TASUKA media successfully enhanced the early writing skills of students at SDN 2 Jombang. This improvement is evident in students’ ability to write various syllables (ka, ki, ku, ko as well as la, li, lu, le, lo) and combine them into words more accurately. The enhancement in writing ability is also reflected in the students’ assignment scores, with an average score of 85, categorized as high. These results demonstrate that TASUKA can serve as an effective instructional tool within the PBL framework, particularly for lower-grade students who depend on concrete media to support their learning processes. Nevertheless, teachers are encouraged to continue innovating and developing instructional media to optimize their use in Indonesian language learning.